(untitled) (Revista Nacional de Odontología, 2014)
Introduction: this is a research paper stemming from the project: “Cephalometric changes observed in patients diagnosed with Class II, Class III, or open bite; or laterognatism treated at the maxillary orthopedic Clinique of the Universidad Antonio Nariño”, the research was conducted in 2008 by the omi (researcher maxillary orthopedists) composed by teachers of the graduate program in Maxillary Orthopedics from the Universidad Antonio Nariño. The goal of the research is stated in the project’s name. Materials and Methods: we made a longitudinal study with a census of 80 patients that were treated at the Maxillary Orthopedics Clinique from 2007 to 2009 who had profile and panoramic X rays taken both at their arrival and at a control six or eight months after the installation of orthopedic apparatuses. To assess changes, we carried out a Bimler cephalometric analysis. Results: the whole sample shows changes in the angle of the 5 and 7 factors, corresponding to the anterior and posterior base of the skull. In adults, we found a tendency to reach the normal established averages. The bone overjet showed changes in this same group after remodeling based on appositions and growth-equivalent resorption that transformed the maxillaries, thus changing their relation. Conclusions: this research confirmed movements at the base of the skull (redirection) and bone growth in the studied group as a response to treatment with maxillary orthopedics.